Evaluation of Essential Oils for the in Vivo Management of Fusarium Tuber Rot Disease of White Yam (Dioscorea rotundata Poir) - Onwuta, Obiora Albert; Dania, Victor Ohileobo (Jordan Journal of Agricultural Sciences, 2025)
Yam is an important economic crop that is widely cultivated in Africa and other sub-tropical continents. Its cultivation is, however, constrained by huge postharvest yield losses in tubers and setts meant for next season planting due to microbial-induced rot. The essential oils (EOs) of three botanicals, Cymbopogon nardus, Ocimum gratissimum and Citrus sinensis were evaluated for their phytochemical composition and efficacy in the management of Fusarium soft rot disease in white yam (Dioscorea rotundata Poir). Chemical constituents were analyzed and quantified using gas chromatography-mass spectrometry (GC-MS) and gas chromatography-flame ionization detectors (GC-FID). The experimental design for the in vivo trial was a 15×3×3 factorial in completely randomized design with three replications, which comprised fifteen isolates of Fusarium oxysporum, three EOs and three concentrations. Geraniol (51.73%), thymol (50.52%) and limonene (45.84%) were the major compounds found in C. nardus, O. gratissimum and C. sinensis EOs, respectively. Rot development in inoculated but treated tubers was significantly (p<0.05) reduced by 9.3 -16.4%, 10.1-17.6% and 10.2-18.3%, respectively at 0.8 ml/ml EO concentration. The efficacy of the EOs in this study indicates their potential as biofungicides in the management of Fusarium soft rot disease in white yam.